ANALISIS KEPUASAN PENGGUNA WEBSITE LIGA ARLOJI MENGGUNAKAN METODE END USER COMPUTING SATISFACTION (EUCS) - Zalukhu, Asni; Nurlela, Siti (INTI Nusa Mandiri, 2026)
The evolution of information technology plays a significant role in accelerating digital transformation across various sectors, including the wristwatch retail industry. The Liga Arloji website is utilized as a medium for promotion and online transactions, which needs to be evaluated in terms of user satisfaction. This study aims to analyze the level of user satisfaction with the performance of the Liga Arloji website using the End User Computing Satisfaction (EUCS) method, in which the components analyzed include five dimensions: content, accuracy, format, ease of use, and timeliness. The methodology of this study is based on a quantitative approach, using a questionnaire as the data collection instrument distributed to 68 selected respondents. The data were processed using the EUCS calculation formula and tested for validity and reliability using SPSS. Based on the data analysis, the findings show that all EUCS dimensions received scores falling into the “Satisfied” to “Very Satisfied” classification. The content dimension achieved an average score of 4.19, accuracy scored 4.13, format scored 4.18, ease of use scored 4.15, and the timeliness dimension received the highest score of 4.22. These findings indicate that user satisfaction with the website is relatively high, particularly in terms of timely information and presented content, while the system’s reliability and accuracy were rated as moderately satisfactory. This study provides several recommendations, including improving data accuracy and enhancing system reliability. The results are expected to serve as a key reference for the future development of e-commerce-based websites